Seed Priming with Salicylic Acid Improves Germination and Growth of Lathyrus sativus L. under Salinity Stress - Sina Siavash MOGHADDAM; Amir RAHIMI; Latifeh POURAKBAR; Faegheh JANGJOO (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
Increasing the ability of crops to maintain growth and productivity under saline conditions is of paramount importance. The effect of salicylic acid (SA) priming on germination and physiological traits of Lathyrus sativus under salinity stress was studied in a factorial experiment based on a completely randomized design. The experimental treatments composed of SA at three levels (0, 0.1, and 0.2 mM) and NaCl salinity at three levels (0, 50, and 100 mM). The effect of salinity level and SA priming was significant on all recorded factors, except from final germination percentage. As salinity level increased, all germination and physiological traits declined compared with control, whereas the mean germination time and percentage of cell death were increased. Moreover, as salinity was intensified, the Hill reaction was decreased significantly. Salinity exhibited the strongest effects at NaCl rate of 100 mM. Seed priming with SA increased germination speed index, reduced mean germination time, and increased leaf relative water content, seedling fresh and dry weight compared with plants from non-primed seeds. Seedling vigor index was increased by 23.4% in primed seeds with 0.2 mM SA. SA priming especially at 0.2 mM rate increased the Hill reaction rate and reduced percentage of cell death. SA priming could be regarded as a practical approach to improve germination traits, seedling growth, and physiological traits of Lathyrus sativus L. under salinity stress conditions.